Importance of durum wheat breeding in terms of bulgur in Southeastern Anatolian Region of Turkey - Tekdal S. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Durum wheat is grown in specific regions of the world, with Turkey being a major producer with 3.5 million tons/year of grain. It has basically been used for the production of bulghur and pasta. Although Turkey is self-sufficient in durum wheat production, the quality falls short of the finest varieties grown in other parts of the world and Turkey has to import better quality varieties to close this quality gap. In Turkey 66.5% of the durum wheat, termed as “macaroni wheat”, is used for making bulghur and the rest for pasta products. Generally, bulghur is used to make “pillaf” as it is cheaper and healthier than rice. The importance of bulghur in human diet is being appreciated and this trend has progressed to Europe and even as far as America. During 2001 about 1 million tons of bulghur was produced by about 500 manufacturing plants throughout the country. In order to meet the demands of industry and consumer preferences, greater importance has been given to durum wheat breeding in Turkey in recent years.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)